Simple and safe liquid seal approach to oxygen-tolerant ATRP. (3rd January 2023) - Du, Yuxuan; He, Congze; Yang, Shicheng; Xu, Chaoran; Pan, Xiangcheng
Graphical abstract: Highlights: A simple and safe liquid seal approach for oxygen-tolerant ATRP. No deoxygenation operations and post-treatment. Sufficient heat and mass transfer allowed at a high stirring speed. Obtained well-defined polymers on a large scale with high conversion. Abstract: Trace oxygen is fatal to the conventional reversible deactivation radical polymerization (RDRP), so it is necessary to eliminate the influence of oxygen through some strict deoxygenation operations or by adding external components (post-treatment required). Here, we report the effective barrier of oxygen dissolution in an open system built by a liquid seal. Two different liquid seal materials, liquid paraffin and lithium grease, are used in this work. Lithium grease materials can stably isolate oxygen at a high stirring speed (450 rpm) to intensify the heat and mass transfer processes during the reaction. An effective atom transfer radical polymerization (ATRP) could be assisted by simply adding liquid seal materials with a thickness of 5 mm, providing polymers with high conversion (≥90 %), controlled molecular weight, narrow molecular weight distribution ( M w / M n  ≤ 1.15) and high end-group fidelity. With this liquid seal strategy, dozens of grams of the polymer were obtained, which is expected to have potential industrial applications under ambient atmosphere and conditions.